2019
DOI: 10.3390/cells8080816
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Target Pathogenetically Relevant Genes and Pathways in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease driven by genetic, environmental and epigenetic factors. Long non-coding RNAs (LncRNAs) are a key component of the epigenetic mechanisms and are known to be involved in the development of autoimmune diseases. In this work we aimed to identify significantly differentially expressed LncRNAs (DE-LncRNAs) that are functionally connected to modulated genes strictly associated with RA. In total, 542,500 transcripts have been profiled in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Total RNA was isolated from PBMC using TRIzol Reagent (Invitrogen, Carlsbad, CA, USA), following the manufacturer's instructions. PCR was performed by following the methods of Dolcino et al [27].…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Total RNA was isolated from PBMC using TRIzol Reagent (Invitrogen, Carlsbad, CA, USA), following the manufacturer's instructions. PCR was performed by following the methods of Dolcino et al [27].…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…All these research studies indicated that lncRNAs are involved in the occurrence and development of various cancers. Furthermore, Dolcino et al [ 13 ] analyzed the transcript profiles of rheumatoid arthritis (RA) patients and healthy donors and found that lncRNA RP11-4989.15 plays an important role in RA pathogenesis. Another study screened eight important lncRNAs interacting with 52 differentially expressed genes enriched in asthma-associated pathways, and these lncRNAs have the potential to serve as underlying biomarkers useful for the future development of therapeutic strategies [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNA), we think that the characteristics of an RNA whether it is translated into a protein or not, cannot influence its possible use as a biomarker, thus we assume that involving this protein-coding gene in the evaluations did not cause bias in our results. HNRNPU was found to be implicated in several processes, including regulation of the innate immunity, proliferation and several diseases like cancers and eosinophilic asthma [ 28 , 29 , 41 45 ]. Our bioinformatic analysis showed that HNRNPU was associated with several FGFR2 related pathways.…”
Section: Discussionmentioning
confidence: 99%